Patents-how much do you need to know to sue?. - Klee, M.M.
How much does the owner of a method patent need to know about a competitor's manufacturing process before bringing a patent infringement suit? Not much-according to the Court of the Appeals for the Federal Circuit (CAFC) in the recent case of Hoffman-La Roche and Syntex (Roche) v. Invamed et al. The case involved the continuing battle between name-brand and generic drug manufacturers. Roche sued eight generic drug manufacturers who were coming out with generic versions of Roche's TICLID(R) brand anti-stroke medicine. The basic patent on TICLID(R) had expired but there were still patents on improved methods for making its active ingredient. Roche's problem was that it could not tell from the finished product whether its patented methods had been used or not
Keywords: Court of the Appeals; Federal Circuit; Hoffman-La Roche; Invamed; Syntex; Active ingredient; Antistroke medicine; Competitor's manufacturing process; Generic drug manufacturers; Method patent owner; Name-brand drug manufacturers; Patent infringement suit; Patented methods; Suing